Physical dosimetry reconstructions of significant radiation exposure at an industrial accelerator facility in Tianjin (China). (10th December 2019) - Ruan, Shuzhou; Huo, Menghui; Su, Kaijun; Liu, Yulian; Yan, Changxin; Zhang, Wenyi; Jiao, Ling
ABSTRACT: The goal of this thesis is to estimate the physical radiation doses for two victims who were accidently exposed to an industrial electron beam at an industrial accelerator facility on 7 July 7 2016 in Tianjin, China. On the basis of the radiation source parameters, irradiation situation and irradiation time, physical dose reconstruction was carried out at the accident site by using a Bottle-Manikin-Absorption (BOMAB) phantom and an Alderson Radiation Therapy (ART) phantom. With thermoluminscent dosimeters (TLDs), skin estimation was conducted for the feet, calves, upper arms, left side of the body and neck, and the mean dose was estimated to be 14.1 ± 5.6 Gy. The foot and leg skin received the highest dose, which was >16.3 Gy. In addition, the mean dose estimated for the eye lens was 0.18 ± 0.07 Gy. The organ effective dose estimated and the total organs effective dose estimated were 0.46–4.94 mSv and 0.21 Sv, respectively. In the course of the accident, the damage caused by the electron radiation field to the exposed person was mainly to the skin, and the contributions to other radiation-sensitive organs were small. The damage to the organs other than the skin was mainly caused by the X-rays generated by the bremsstrahlung of the electron beam from the environment or the human body.